2023
DOI: 10.3390/ijerph20043232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Whole-Body Vibration Training on Hemorheological Blood Indices in Young, Healthy Women

Abstract: The aim of the study is to assess the effect of single and 12-week WBVT and training without vibration on changes in hemorheological blood indices and plasma fibrinogen levels in young, healthy women. Three groups are distinguished: the experimental group—participating in WBVT (n = 17); the comparison group—implementing the same physical exercise protocol without the vibration factor (n = 12); and the control group—no intervention (n = 17). In the experimental and comparison group, blood is collected before an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 37 publications
0
1
0
Order By: Relevance
“…Originally, vibration stimulus was used for healing and therapeutic purposes in order to achieve an analgesic effect. The studies performed in the following years showed that vibration can also have other beneficial effects, e.g., metabolic processes regulation, reduction of fibrinogen levels, normalization of the vascular system, and activation of muscle spindles (for review, see [13][14][15][16][17]). Subsequent projects have also shown the safety of this physical stimulus, and the list of contraindications for the use of treatments based on vibration is relatively short [18].…”
Section: Introductionmentioning
confidence: 99%
“…Originally, vibration stimulus was used for healing and therapeutic purposes in order to achieve an analgesic effect. The studies performed in the following years showed that vibration can also have other beneficial effects, e.g., metabolic processes regulation, reduction of fibrinogen levels, normalization of the vascular system, and activation of muscle spindles (for review, see [13][14][15][16][17]). Subsequent projects have also shown the safety of this physical stimulus, and the list of contraindications for the use of treatments based on vibration is relatively short [18].…”
Section: Introductionmentioning
confidence: 99%
“…Similar studies were carried out in a group of elderly men subjected to a series of thirty vibration sessions, also on the Metabolism module, and a decrease in fibrinogen was confirmed in the group with the vibration applied, while in the control group, an increase in fibrinogen concentration was shown during the period of observation [27]. However, relatively few studies show the influence of vibration treatments on fibrinogen concentration and changes in rheological parameters of the blood [10,52]. Ghazalian et al [53], after 5 weeks of vibration treatments, demonstrated an indirect effect of vibration treatments on the level of fibrinogen concentration by enhancing endothelial function.…”
Section: Discussionmentioning
confidence: 54%